Muster points - Crawford, Lucas (Brave & brilliant series, 2023)
"A journey through COVID, small rooms and big cities, hungers and healing, all via the power, pleasure, and pain of queer and trans worldmaking. In March 2020, Lucas Crawford was quarantined at the Banff Centre for the Arts, coughing like a good fat asthmatic at high altitude, ending a relationship, not knowing when or how he would get home, or where home would be when he got there. What does a writer do, stranded in a dorm room, unsure of the future? Write poems. Muster Points is a frank discussion of desire, nostalgia, mental illness, and health from a professor with one foot kicking the ivory tower and both feet sloshing in all the sundry fluids of queer sex and depression. These poems bring us on a trans boy's trips through the shard-sharp ruins of heterosexual marriages, into weird rural masculinities and their fraught survival, into regret and recovery, durability and desire. This book takes readers to the core of Crawford's sexual politic, through his front door and to the back of his mind. As Crawford packs his two suitcases and bangs into past selves, tenuous futures, and a global emergency, he tracks his collisions toughly and tenderly, documenting every relic and clue. Muster Points arouses and provokes, uses visceral language and unequivocal vulnerability to conjure places of retreat and relief amidst emergency. Like the green and yellow signs that bear the book's title, Muster Points invites readers to congregate in the spaces where Crawford gathers strength. Join him there!"--